(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
This paper deals with some properties of fuzzy path connectedness and maximal fuzzy path connectedness on a fuzzy topological space by means of fuzzy points. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 1, 67-71, 2018